The Role of Item-Specific Information for the Retrieval Awareness of Performed Actions - Li, Guangzheng; Wang, Lijuan (Frontiers in Psychology, 2018)
Research on action memory has been pursued for more than 30 years, but it is still unclear what drives the recollection process of performed actions. In this study, we used the remember/know paradigm and designed two experiments to examine the relation between item-specific processing and retrieval awareness of subject-performed tasks (SPT). The results showed that SPT allows remember responses in remember-know judgments more easily; that is, SPT can enhance the frequency of recalling re-collective experience. Item-specific processing can improve the memory performance and the proportion of remember judgments of verbal tasks (VT), but it does not improve the memory performance and proportion of remember judgments of SPT, indicating that SPT can enhance item-specific processing, which leads to more remember responses in judgment. The relation between item-specific processing and retrieval awareness of SPT is also discussed.